ON THE WAYS OF USING OF THE METHODS OF PROCESSING OF MICROSTRUCTURES IMAGES FOR SOLVING OF PROBLEMS ON REVEALING OF INTERRELATIONS OF TYPE «MICROSTRUCTURE - PROPERTIES» - A. N. Chichko; O. A. Sachok; V. F. Sobolev; S. G. Lihouzov; O. I. Chichko; A. V. Vedeneev (Литьë и металлургия)
The interrelation between microstructure characteristics, defined on the basis of its computer image and properties of industrial facilities, produced at RUP «BMZ» is investigated.